Research status and future prospects on ultraviolet Ad-Hoc network - GUO Jia; YUAN Renzhi; WANG Siming; PENG Mugen; YANG Chuang (Dianxin kexue)
Ultraviolet Ad-Hoc network integrates the advantages of ultraviolet communication, including low background radiation, non-line-of-sight (NLOS) communication, high local security, and strong adaptability to various climatic conditions, along with the benefits of rapid deployment and high flexibility in Ad-Hoc network. These features make it a key technology for the practical development of ultraviolet communication. Although significant progress has been made in ultraviolet Ad-Hoc network research, several challenges remain. These include self-interference issues in the physical layer due to the full-duplex mode, node energy consumption and synchronization problems in the data link layer’s media access control (MAC) protocol, and poor network connectivity and scalability of routing protocols in the network layer. Based on this, the research status in the physical layer, data link layer, and network layer of ultraviolet Ad-Hoc network were reviewed, and the future development directions were also prospected.